Analysis of Legal Protection for Recipients of Fintech Funds based on Financial Services Authority Regulation Number 10/POJK.05/2022 - Farhan Restu Ernanda; Wardah Yuspin (Universitas Muhammadiyah Surakarta, 2023)
Technological acceptance of funds is increasingly widespread. Fi‐nancial Technology does not receive legal protection even though the Fi‐nancial Services Authority Regulation Number 10/POJK.05/2022 has been issued, but this legal protection is still considered by many recipients of funds as not legally protected.The results of this research discuss the procedures for receiving funds by financial technology consumers and the legal protection provided to recipients of financial technology funds. This study divides the legal protection into two parts, namely preventive legal protection and repressive legal protection, and is analyzed according to the legal regulations that apply to recipients of funds.This research uses the normative legal research method which is carried out by analyzing the current regulations. The purpose of this research is to find out whether the Financial Services Authority Regulation Number 10/POJK.05/2022 has provided adequate legal protection for service recipients and recipients of funds in digital financial transactions.